Electrostatics, structure prediction, and the energy landscapes for protein folding and binding - Tsai, Min‐Yeh (Protein Sci, 2015)
While being long in range and therefore weakly specific, electrostatic interactions are able to modulate the stability and folding landscapes of some proteins. The relevance of electrostatic forces for steering the docking of proteins to each other is widely acknowledged, however, the role of electrostatics in establishing specifically funneled landscapes and their relevance for protein structure prediction are still not clear. By introducing Debye‐Hückel potentials that mimic long‐range electrostatic forces into the Associative memory, Water mediated, Structure, and Energy Model (AWSEM), a transferable protein model capable of predicting tertiary structures, we assess the effects of electrostatics on the landscapes of thirteen monomeric proteins and four dimers. For the monomers, we find that adding electrostatic interactions does not improve structure prediction. Simulations of ribosomal protein S6 show, however, that folding stability depends monotonically on electrostatic strength. The trend in predicted melting temperatures of the S6 variants agrees with experimental observations. Electrostatic effects can play a range of roles in binding. The binding of the protein complex KIX‐pKID is largely assisted by electrostatic interactions, which provide direct charge‐charge stabilization of the native state and contribute to the funneling of the binding landscape. In contrast, for several other proteins, including the DNA‐binding protein FIS, electrostatics causes frustration in the DNA‐binding region, which favors its binding with DNA but not with its protein partner. This study highlights the importance of long‐range electrostatics in functional responses to problems where proteins interact with their charged partners, such as DNA, RNA, as well as membranes.